2014
DOI: 10.3389/fncel.2014.00429
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse axonal injury in brain trauma: insights from alterations in neurofilaments

Abstract: Traumatic brain injury (TBI) from penetrating or closed forces to the cranium can result in a range of forms of neural damage, which culminate in mortality or impart mild to significant neurological disability. In this regard, diffuse axonal injury (DAI) is a major neuronal pathophenotype of TBI and is associated with a complex set of cytoskeletal changes. The neurofilament triplet proteins are key structural cytoskeletal elements, which may also be important contributors to the tensile strength of axons. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 141 publications
2
95
0
Order By: Relevance
“…Recently, we showed that PAD exposure is a mechanism by which tau can directly impair anterograde fast axonal transport (23, 24, 27), which could contribute to axonal dysfunction and eventually neurodegeneration (31, 64). Axonal dysfunction is a prominent feature of traumatic brain injury-related pathology and several lines of evidence from animal models, culture models, and human traumatic brain injury cases support a primary role for axonal dysfunction in posttraumatic neurodegeneration (6568). In this study, we identified PAD-exposed tau, oligomeric tau, and phospho-S422 tau in the axonal pathologies of CTE.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that PAD exposure is a mechanism by which tau can directly impair anterograde fast axonal transport (23, 24, 27), which could contribute to axonal dysfunction and eventually neurodegeneration (31, 64). Axonal dysfunction is a prominent feature of traumatic brain injury-related pathology and several lines of evidence from animal models, culture models, and human traumatic brain injury cases support a primary role for axonal dysfunction in posttraumatic neurodegeneration (6568). In this study, we identified PAD-exposed tau, oligomeric tau, and phospho-S422 tau in the axonal pathologies of CTE.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] DAI is often accompanied by cytoskeletal alterations, such as the presence of varicosities and swellings along terminal bulbs and axons. [8][9][10] Furthermore, the elevated level of Ca2+ in the mitochondria can promote the synthesis of reactive oxygen species (ROS), thus increasing the levels of oxidative stress in axons. [8][9][10] Furthermore, the elevated level of Ca2+ in the mitochondria can promote the synthesis of reactive oxygen species (ROS), thus increasing the levels of oxidative stress in axons.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Such cytoskeletal alterations may be induced by mechanical damages and subsequent Ca2+ influx through the disruptions in the axolemma. 10 In fact, oxidative stress can be induced by the disruption of the equilibrium between various biochemical processes, thus leading to dysfunction in nonenzymatic and enzymatic cellular defense systems against oxidation. 10 In fact, oxidative stress can be induced by the disruption of the equilibrium between various biochemical processes, thus leading to dysfunction in nonenzymatic and enzymatic cellular defense systems against oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…congruous homonymous incomplete hemianopia ( Figure 1B), a finding that is consistent with axonal deterioration over a 6-month period. 9 Macular optical coherence tomography (OCT) showed atrophy of the ganglion cells in the right side of both maculae, indicating anterograde degeneration of the visual pathway (Figure 2). On the other hand, OCT of the optic disc showed atrophy of nerve fibres superiorly and inferiorly in both eyes and also nasally in the LE.…”
Section: Case Descriptionmentioning
confidence: 99%